Transumblical Single Incision Two-Port Laparoscopic Assisted Appendectomy: Early Experience in Paediatric Patients (TAJ: Journal of Teachers Association, 2009)
Laparoscopic appendectomy considered as superior alternative to open appendectomy. Usual laparoscopic appendectomy is performed with the three port system. In this study, we performed a unique single transumblical incision two-port laparoscopic assisted appendectomy with the aim to reduce postoperative port site complication as well as improving cosmesis and patients satisfaction. From January 2010, 32 patients were admitted with clinically diagnosed acute appendicitis and were randomly assigned to single transumblical incision two-port laparoscopic assisted appendectomy. Transumblical single incision two-port laparoscopic assisted appendectomy was attempted in all patients (9 males and 23 females) with an average age of 9.2 years. Transumblical single incision two-port laparoscopic assisted appendectomy was successfully completed in 31 patients. In one patient, another additional port required due to severe adhesion of the appendix. Mean operation time was 25.2 minutes (range, 17-38), and mean postoperative hospital stay was 1.Sdays (range 1-2). Postoperative complications (local pericaecal abscess) occurred in one case that was treated conservatively. Transumblical single incision two-port laparoscopic assisted appendectomy appears to be a feasible and safe technique for the treatment of acute appendicitis in the paediatric setting. It allows nearly scar less abdominal surgery. The true benefit of the technique should be assessed by randomized controlled trials.TAJ 2009; 22(1): 289-294